Trifunctional organolithium initiator for living anionic polymerization in hydrocarbon solvents in the absence of polar additives - George V. Theodosopoulos; Christopher M. Hurley; Jimmy W. Mays; Georgios Sakellariou; Durairaj Baskaran (Polymer Chemistry, 2016)
A novel hydrocarbon-soluble trifunctional organolithium initiator, with no polar-additive requirements, has been synthesized for use in anionic polymerization. The complete synthesis of the unsaturated tri-diphenylethylene compound, 4,4,4-(ethane-1,1,1-triyl)tris(((3-(1-phenylvinyl)benzyl)oxy)benzene) (I), is described and the eﬃciency of the new initiator is evaluated using 1H NMR and Nano-assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (NALDI-TOF MS). Activation of precursor I, was performed in situ using stoichiometric amounts of sec-BuLi in benzene. Three-arm polystyrene and polyisoprene stars with narrow molecular weight distributions were obtained in the case of relatively high total anion concentration, [sec-BuLi]0 > 3.8 × 10−3 mol L−1 (3 × [I]0). At low total anion concentrations, uncontrolled molecular weight and broad/bimodal distributions were obtained, plausibly attributed to the presence of partially solvated aggregation dynamics complicating the propagation. The ‘living’ nature of the polymerization was conﬁrmed by the sequential polymerization of styrene, and isoprene. The viscometric branching factor g’ values of the ﬁnal branched polymers were measured and compared to g’ values of three-arm stars reported in the literature.